2021
DOI: 10.48550/arxiv.2105.14569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical complexity of phosphorous bearing species in various regions of the Interstellar medium

Milan Sil,
Satyam Srivastav,
Bratati Bhat
et al.

Abstract: Phosphorus related species are not known to be as omnipresent in space as hydrogen, carbon, nitrogen, oxygen, and sulfur-bearing species. Astronomers spotted very few P-bearing molecules in the interstellar medium and circumstellar envelopes. Limited discovery of the P-bearing species imposes severe constraints in modeling the P-chemistry. In this paper, we carry out extensive chemical models to follow the fate of P-bearing species in diffuse clouds, photon-dominated or photodissociation regions (PDRs), and ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
(176 reference statements)
1
3
0
Order By: Relevance
“…However, theoretically calculated binding energies for HS, PH 3 , or PH 2 on water ice are available: 2700 K for HS (Wakelam et al 2017), 2200 K for PH 3 , and 1800 K for PH 2 (mean values; Molpeceres & Kästner 2021). Sil et al (2021) and Nguyen et al (2021) also calculated the binding energy of PH 3 on water ice and reported a value similar to that of Molpeceres & Kästner (2021). In our model, we neglect thermal desorption and thermal hopping of H 2 S, HS, PH 3 , and PH 2 .…”
supporting
confidence: 69%
See 1 more Smart Citation
“…However, theoretically calculated binding energies for HS, PH 3 , or PH 2 on water ice are available: 2700 K for HS (Wakelam et al 2017), 2200 K for PH 3 , and 1800 K for PH 2 (mean values; Molpeceres & Kästner 2021). Sil et al (2021) and Nguyen et al (2021) also calculated the binding energy of PH 3 on water ice and reported a value similar to that of Molpeceres & Kästner (2021). In our model, we neglect thermal desorption and thermal hopping of H 2 S, HS, PH 3 , and PH 2 .…”
supporting
confidence: 69%
“…Like the gas-phase formation of H 2 S, the formation of PH 3 via gas-phase reactions is inefficient (Thorne et al 1984). Thus, the main formation pathway for gas-phase PH 3 is the formation of PH 3 ice by the sequential hydrogenation of atomic P on grain surfaces, followed by thermal or nonthermal desorption, as assumed in previous astrochemical models (e.g., Charnley & Millar 1994;Aota & Aikawa 2012;Chantzos et al 2020;Sil et al 2021).…”
Section: Astrochemical Implicationsmentioning
confidence: 96%
“…Detailed chemical modeling has been carried out to study the abundances of the species observed in G31. Our Chemical Model for Molecular Cloud (CMMC) (Das et al, 2015a(Das et al, ,b, 2016Gorai et al, 2017a,b;Sil et al, 2018;Gorai et al, 2020;Sil et al, 2021;Das et al, 2021) is considered for this modeling. 2013) and infall velocity variation is derived from the Equation 1 by using v 1000 = 4.9 km s −1 .…”
Section: Chemical Modelingmentioning
confidence: 99%
“…The time evolution of the physical parameters (H 2 density and temperature) are considered in three significant steps: isothermal collapsing phase, warm-up phase, and post-warmup phase. This type of straightforward model is best suited to study the chemical evolution of hot cores (Gorai et al, 2020;Sil et al, 2021). As discussed in Section 2.2, the gas cloud envelope is divided into 23 spherical shells.…”
Section: Chemical Modelingmentioning
confidence: 99%